Acute interstitial nephritis related to immune checkpoint inhibitors - Belliere, Julie (Br J Cancer, 2016)
BACKGROUND: Immune checkpoint inhibitors (anti-PD1 or anti-CTLA-4) are increasingly used in various cancers. Immune checkpoint inhibitors (ICI)-related renal disorders are poorly described (9 cases) and were only related to Ipilimumab. METHODS: Retrospective collection of clinical charts of all the patients admitted for renal disorders following ICI in the University Hospital of Toulouse (France). RESULTS: We report on adverse renal events that occurred in three patients treated with anti-PD1 (nivolumab or pembrolizumab) or anti-CTLA-4 (ipilimumab). Acute kidney injury occurred at 4–12 weeks after initiation of treatment, and harbored features of tubulo-interstitial nephritis (interstitial polymorphic inflammatory infiltrate with predominant CD3+ CD4+ T cells, associated with granuloma in one). Following withdrawal of ICI and steroid intake, estimated glomerular-filtration rate had improved in all patients. CONCLUSIONS: These data suggest that all ICI can lead to acute interstitial nephritis, possibly related to the presence of autoreactive clonal T cells. We recommend that patients receiving ICI should undergo renal monitoring every 2 weeks for 3–6 months.